The The current status of Henckelia peduncularis (Gesneriaceae): Taxonomy, typification, distribution and IUCN Red List assessment - Maity, Rohan; Chowlu, Krishna; Dash, Sudhansu Sekhar (Phytotaxa, 2024)
The long lost Henckelia peduncularis (Gesneriaceae), was hitherto known from its type specimens collected from Burma, in 1926. Recently described Henckelia dasii from Arunachal Pradesh, India; revealed substantial similarities with the aforementioned Burmese element. Morphological analyses based on the type specimens of both the names revealed H. dasii is appropriate to be reduced as a heterotypic synonym of H. peduncularis. The present article also deals with the Red List assessment of H. peduncularis based on IUCN criteria and lectotype designation for the name Chirita peduncularis B.L. Burtt.